Control of perioperative pain - D. Arbuck (Вестник анестезиологии и реаниматологии)
Objective: analysis of the current pharmacological approaches to perioperative pain control, including in patients with chronic pain and opioid dependenceResults: An assessment of pregabalin, gabapentin, celecoxib, and other medications utilized in perioperative pain control as well as a characterization of methods used in pain control in opioid-dependent individuals, including chronic buprenorphine therapy. Detailing how multiple preparations are employed and their effectiveness in intraoperative and postoperative pain management. Also, addressing the increased role of pharmacogenomics in individualized pain management.